Enhancing eye disease classification through synergistic deep learning approaches - Rahaman, Asif; Mahamud, Shifat; Akter, Shanjida; Saha, Dipro; Fahad (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.